The Effect of Digital Banking, Digital Transformation on the Efficiency of Commercial Banks in Indonesia - Sugihyanto, Toto; Jansen Arsjah, Regina (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2023)
The purpose of this paper is to assess the efficiency of the general banking industry in Indonesia on the use of digital banking and digital transformation. This paper is a research paper with quantitative methods and uses primary data collected by researchers using questionnaires. As for the data analysis method with PLS software SmartPls. The respondents were employees of commercial banks consisting of ten Islamic commercial banks and eleven conventional commercial banks. Findings - Investigative findings show that the banking industry in Indonesia is generally on a trend of increasing efficiency after implementing digital banking and digital transformation. And Financial Innovation does not moderate digital banking and digital transformation towards efficiency. This study provides a basis for regulators and bankers to improve efficiency in the banking sector by improving services to customers through the application of digital banking and digital transformation in order to improve banking performance. Originality/value – This paper presents new empirical findings on the state of efficiency of Commercial Banks in Indonesia after using digital banking and digital transformation.